PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT PEGADAIAN (PERSERO) BATAM - Syaifullah Syaifullah; Mira Mira (Universitas Putera Batam, 2018)
The purpose of research is to know the partial influence (T test) and simultaneously (F test) between brand image variable and service quality to customer satisfaction PT Pegadaian (Persero) Batam. The research method used in this research is descriptive research method with quantitative approach Data collection techniques were done by distributing questionnaires to each respondent as much as 294 respondents. The results showed that the value of R Square of 0,135 or 13,5% of the value can be known the brand image and service quality affect the customer satisfaction of 13,5% while the rest is 86,5% influenced by other factors not examined. The result of research based on t test for brand image has value equal to 6,080 > 1,968 (t table) and significant value 0,000 <0,05 meaning that variable of brand image have significant effect to customer satisfaction, while service quality has value of 2,281 > 1,968 (t table) and significant value 0,023<0,05 meaning service quality variable have significant effect to customer satisfaction. And the result of F test has value equal to 22,670>3,03 (F table) and significant value 0,000 <0,05 can be interpreted that variable brand image and service quality simultaneously have significant effect toeffect to customer satisfaction.